Inter-organizational Integration among Public Sector Organizations of Oromia Regional State - Olani, Dereje (African Journal of Leadership and Development, 2021)
Nowadays, giant forces such as resource scarcity, technological changes, population growth and increasing demand for quality services force organizations to collaborate. This study, thus, aims to assess the practice of inter-organizational integration among the public sectors of Oromia National Regional State. Mixed design and probabilistic and non-probabilistic sampling techniques were used. Employees at Oromia Regional State especially regional bureau level employees were the participants of the study. Data were collected from both primary and secondary sources. Based on some characteristics and important nature of public sectors about 8 bureaus were selected purposefully since they are expected to provide a more robust and reliable data. Questionnaires and interviews were used to gather first hand data. Descriptive and inferential statistics were used to analyze and discuss the findings. The finding of the study showed that there was moderate but inadequate practice of inter-organizational integration as the result of constraints such as poor resource sharing, failure to set significant goal and shared learning and so forth. A correlation analysis indicated that resource and setting significant goal have strong positive relationship with inter-organizational integration in the study area. The study implies that there was poor institutionalization of inter-organizational integration among the public sectors. Hence, institutionalizing inter-organizational integration would help to solve complex public problems.